Envelhecimento populacional e migração: um olhar sobre instituições de longa permanência étnicas em São Paulo e Rio Grande do Sul e a migração de aposentados norte-americanos para Cuenca, Equador - Valle, Ida Raichtaler do (2022)
This thesis aims to focus on the history of aging in its philosophical, social and economic understanding, with an emphasis on the different forms of existence of the elderly from generational, social, race and ethnicity and cultural perspectives. Population aging is an overall social fact, and the experiences related to the passage of time occur in different ways. The world population aged 60 years and over will triple by 2050, especially in underdeveloped countries like Brazil, which historically housed younger populations compared to more advanced age groups, but since the 1970s, with the influence of new cultural, social and economic paradigms, began to reduce fertility and mortality rates and increased life expectancy among the elderly. In this sense, it is urgent to reflect on the aging process and access to rights in the Brazilian territory and in underdeveloped countries. Social inequality directly affected the life expectancy and social wellbeing of the elderly, as demonstrated during the COVID-19 pandemic, a period in which aging populations were directly negatively affected. This paper presents a study based on multi-site interviews in ethnic communities of Jewish Long-term Care Institutions in São Paulo and Rio Grande do Sul, when the international migration of the late nineteenth century in Brazil redesigned the country's demography and created new spaces to house elderly Jews. It is also discussed the fact that developed countries such as the USA do not have all the necessary equipment to provide quality accommodation for their elderly who, in the search for a more peaceful life in a less violent country, decide to migrate in order to enjoy their pensions in other underdeveloped, countries, as in the case of the city of Cuenca, Ecuador. With this research, I intend to present the diversity of aging, especially addressing the social transformations that the elderly population causes in the places where they live, using the theme of migration as a focal point of demographic changes and paradigms of the idea of progress, using the example of elderly people of Jewish origin in Brazil who live in Longterm Care Institutions, and in the analysis of the North American retirees from middle and working classes who migrated to Ecuador, South America